Identifikasi Gangguan Open Circuit Dan Short Circuit Pada Instalasi Photovoltaic Array Dengan MPPT Berbasis Artificial Neural Network - Khalin Khalin; Sutedjo Sutedjo; Dimas Okky Anggriawan (Energi & Kelistrikan, 2022)
In the field of photovoltaic, the last few years have been very hotly discussed and researched as a new renewable source to produce electricity that cannot be exhausted. In the development effort there must be some problems arising from the existence of a new system. As with open circuit and short circuit interference. Therefore, The Identification of Open Circuit and Short Circuit Interference in Photovoltaic Array Installation with MPPT Based Artificial Neural Network is present to solve the problem. For identification of the location of the disruption is carried out on each photovoltaic string by knowing the voltage and current when there is an open circuit or short circuit interference, as well as the output power of the MPPT is used to determine the type of interference that occurs. Identification of interference using the Artificial Neural Network method with the purpose of this system can find out the location of interference and the type of open circuit or short circuit interference in photovoltaic array installations with MPPT. So that it is easy to know the location of the disturbance that is useful to maximize handling quickly and precisely. Keywords: Photovoltaic array, open circuit, short circuit, MPPT, Artificial Neural Network ABSTRAK Dalam bidang photovoltaic, beberapa tahun terakhir sangat hangat menjadi perbincangan dan penelitian sebagai sumber baru terbarukan untuk menghasilkan energi listrik yang tidak bisa habis. Dalam upaya pengembangnnya pasti ada beberapa permasalahan yang timbul dari adanya sistem baru. Seperti halnya adanya gangguan open circuit dan short circuit. Maka dari itu, Identifikasi Gangguan Open Circuit dan Short Circuit pada Instalasi Photovoltaic Array dengan MPPT Berbasis Artificial Neural Network hadir untuk menyelesaikan masalah tersebut. Untuk identifikasi lokasi gangguan dilakukan pada setiap string photovoltaic dengan mengetahui tegangan dan arus ketika terjadi gangguan open circuit maupun short circuit, serta daya keluaran dari MPPT digunakan untuk mengetahui jenis gangguan yang terjadi. Identifikasi gangguan menggunakan metode Artificial Neural Network dengan tujuan sistem ini dapat mengetahui lokasi gangguan dan jenis gangguan open circuit atau short circuit pada instalasi photovoltaic array dengan MPPT. Sehingga memudahkan untuk mengetahui lokasi gangguan yang berguna untuk memaksimalkan penanganan secara cepat dan tepat. Kata kunci: Photovoltaic array, open circuit, short circuit, MPPT, Artificial Neural Network